Factors Associated with Complaints of Low Back Pain in Areca Peeling Workers - Entianopa, Entianopa; Harahap, Putri Sahara; Junaidi, Muhammad (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: An unnatural working attitude causing the body to deviate from its default posture is one of the contributing factors to the low back pain (LBP) experienced by workers. For instance, areca peeling workers often adopt a posture of sitting hunched over for extended periods. Therefore, this research aimed to identify factors related to a history of LBP among areca peeling workers in Dataran Pinang Village, Kuala Betara District, West Tanjung Jabung Regency. Methods: Using a sample size of 66 respondents, this quantitative research adopted a cross-sectional design and a simple random sampling method. The instruments used included questionnaires, observation, and documentation, and the data were analyzed both univariately and bivariately, with chi-square analysis as the statistical test. Results: The statistical analysis showed no correlation between work time, work duration, repetition, and LBP. However, there was a correlation between LBP and work attitude (0.051<0.05) in areca peeling workers. Conclusion: A relationship exists between work attitude of areca peeling workers and the occurrence of LBP. Therefore, it is advisable for workers who experienced complaints of LBP to perform tasks correctly. This approach would reduce the number of repetitive activities (repetitions) conducted.